Envisioning architecture : drawings from the Museum of Modern Art - 10213 Museum of Modern Art (New York, N.Y.); McQuaid, Matilda; Royal Academy of Arts (Great Britain); Schirn Kunsthalle Frankfurt; Museu Serralves (New York : Museum of Modern Art, 2002)
02